Caracterização de isolados de Fusarium oxysporum e resistência de genótipos de Passiflora à fusariose - Teixeira, Letícia Magalhães (2015)
Brazil is the major passion fruit producer in the world, and collar rot of Passiflora edulis f. flavicarpa, caused by Fusarium spp., is one of the limiting problems of the crop, significantly reducing yield. Although yellow passion fruit is propagated by seeds, the use of rootstocks tolerant to early death could be a management strategy for cultivation in areas with disease history. Thus, this study characterized Fusarium isolates obtained in Triângulo Mineiro and determined the most suitable genotype to use for grafting to reduce losses caused by fusariosis. Fusarium sp. isolates were obtained from symptomatic plants in commercial areas of Uberlândia, District Cruzeiro dos Peixotos (Uberlândia), Indianópolis and Prata, MG. Fungal isolation was done in PDA and 10 days later, mycelial fragments were transferred to CMA (Corn Meal Agar). Patogenicity test was done in 45-days-old Passiflora edulis seedlings. Sporulation in three different growth media was quantified by counting in Neubauer chamber 10 days after transferring mycelial disks to malt extract-agar 2%, PDA and CMA, in a completely randomized design as a factorial 4X3 with five replications. The isolates were incubated in Petri plates at 22 ± 3ºC and 12 hours lighting to stimulate myceliogenic growth. Characterization of morphological structures of isolates was done with minimum cultivation in Malt extract-agar 2% amended with sterilized soil + sand (1:1). Mycleial growth was determined by measuring colony diameter in PDA (Potato Dextrose Agar 39 g L-1), Malt extract Agar 2% and CMA (17 g L-1) 10 days after incubation, as a 4 x 3 factorial, with 5 replications. Five days later the color of the colonies was evaluated. Three Passiflora species and two seedling types were used to evaluate field resistance to fusariosis, in a randomized block design, as a 3X2 factorial, with three Passiflora species (Passiflora alata, P. setacea and P. edulis) and two seedling types (ungrafted or grafted with P. edulis). All isolates obtained were pathogenic to P. edulis. The best medium for conidium production was Malt extract and most sporulating isolates were LMT01 (AL) and LMT02 (GU). Isolate color varied from white to pink to violet. PDA was the the medium that least favored mycelial growth of the isolates. Only LMT02(GU) and LMT04(IN) formed macro and microconidia. Shape, dimensions and septa number of macroconidia and microconidia, as were as the presence of characteristic monophyalides allowed the classification of all isolates as Fusarium oxysporum f.sp. passiflorae. Passiflora alata and P. setacea, used as rootstocks for P. edulis in the field, were resistant to fusariosis. Although ungrafted P. edulis does not survive in areas infested with the pathogen, its use as a rootstock promoted, similarly to P. setacea, greater growth of secondary branches 180 days after transplanting to the field.